Food System Actors engaged in the cocreation of agroecological innovations: Results of three years of engagement in eight countries - Staiger, Simone; Orjuela, Guillermo (2024)
The CGIAR initiative on Agroecology has been actively engaging with food system actors (FSA) in eight countries (Burkina Faso, India, Kenya, Lao PDR, Peru, Senegal, Tunisia, and Zimbabwe) to codesign, test, and adapt agroecological innovations, both technological and institutional, from food production to consumption. At the core of the Initiative is the necessity to generate scientific evidence that shows how agroecological principles applied in different socio-ecological systems are better able to provide equity, productivity, economic and environmental benefits than alternatives, including the status quo. The engagement takes place in Agroecological Living Landscapes (ALLs) that are formed in selected territories of each country with diverse food system actors (FSA): farmer associations or communities, researchers from multiple disciplines, extensionists, private companies, international and national non-governmental organizations as well as local, regional, and national policymakers. The establishment of ALLs does not follow a standard methodology: Each country’s context and a participatory vision-to-action process leads to a different agroecological transition pathway(s) and multi stakeholder approaches. The engagement of food system actors is addressed in the monitoring, evaluation, learning and impact assessment (MELIA) component of the Initiative. Country teams collected and reported data quarterly in a dedicated web-based application regarding engaging activities. FSA engage with the initiative when they participate in diverse activities that aim at assessing, co-designing and testing agroecological innovations at farm, market and policy levels. The co-creation process consists in FSA working together and having an equal voice in the activities that aim at developing agroecological innovations. Agroecological innovations in turn are of technological and institutional nature and concern the broad range of Agroecological principles (agroecological principles as defined in HLPE, 2019).